Determinan kejadian pemasangan ulang double lumen catheter pada pasien dengan penyakit ginjal kronis - Riris Andriati; Dewi Fitriani; Liza Puspa Dewi; Yuliastuti Yuliastuti (Holistik Jurnal Kesehatan, 2021)
Determinants of double lumen catheter reimplantation in patients with chronic kidney diseaseBackground: Double Lumen catheter is a sterile tube that is inserted into a large central vein such as the jugular vein, subclavian vein or femoral vein through a surgical procedure. Failure of hemodialysis due to positional dysfunction and double lumen catheter infection must be reimplanted so that the hemodialysis continues on schedule.Purpose: To determine the relationship of factors that affect reattachment of the double lumen catheter in patients with chronic renal failure in BSD Medika Hospital.Method: A descriptive quantitative analytic with cross sectional design. Subjects were chronic kidney disease patients who performed regular hemodialysis through double lumen hemodialysis catheter access. Risk factor variables (age, sex, hypertension, DM, history of infection, location of insertion, duration of use, history of previous double lumen catheter placement). The research sample was 32 respondents.Results: Bivariat results, age (p = 0.637); gender (p = 1.000); status of hypertension (p = 0.338); status of infection (p = 0.138); status of Diabetes Mellitus (p = 0.053); insertion location (p = 0.052); duration of use (p= 0.004).Conclusion: There is a significant correlation between duration of use and reimplantation of double lumen catheter in patients with chronic kidney disease.Keywords: Double lumen catheter; Reimplantation; Patients; Chronic kidney diseasePendahuluan: Double lumen catheter adalah suatu selang steril yang dimasukan kedalam vena sentral besar seperti vena jugularis, vena subklavia atau vena femoralis melalui prosedur operasi. Kegagalan hemodialisa yang dikarenakan disfungsi posisi dan infeksi double lumen catheter maka harus dilakukan pemasangan ulang kateter agar hemodialisa tetap dilaksanakan sesuai jadwal.Tujuan: Mengetahui adanya hubungan faktor-faktor yang memengaruhi pemasangan ulang double lumen catheter pada pasien penyakit ginjal kronik di RS Medika BSD.Metode: Penelitian deskriptif analitik kuantitatif dengan desain cross sectional. Variabel yang digunakan adalah usia, jenis kelamin, riwayat hipertensi, riwayat DM, riwayat infeksi, lokasi insersi, lama penggunaan, dan riwayat pemasangan double lumen catheter sebelumnya. Subyek penelitian adalah pasien dengan penyakit ginjal kronis yang dilakukan hemodialisis reguler melalui akses vaskular kateter hemodialisis double lumen. Sampel penelitian sebesar 32 responden.Hasil: bivariat analisis menunjukkan hasil: usia (p=0.637); jenis kelamin (p=1.000); riwayat hipertensi (p=0.338); riwayat infeksi (p=0.138); riwayat DM (p=0.053); lokasi insersi (p=0.052); dan lama penggunaan (p=0.004).Simpulan: Lama penggunaan berhubungan signitifikan dengan pemasangan ulang catheter double lumen pada pasien gagal ginjal kronik di RS Medika BSD Kota Tangerang Selatan.